Aural symptoms in temporomandibular disorder patients - Ahmad A Al-Tuhaf (University of Mosul, College of Dentistry, 2005)
Abstract The prevalence of aural symptoms in 100 patients with temporomandibular disorder (TMD) were investigated and compared with control group of 100 subjects without clinical manifestation of TMD. The relationship between otologic symptoms and severity of TMD signs was also evaluated. Examination of temporomandibular joint (TMJ) included maximum mouth opening, clicking, crepitation, locking, luxation, deviation of midline, masticatory muscle tenderness, and TMJ tenderness. All patients of the two groups were questioned about feeling of ear complaints, including otalgia, tinnitus, and hearing loss. It was found that 48% of TMD patients complained of one or more aural symptoms compared with 13% of the controls. There was a highly significant difference between the two groups (p<0.01). The prevalences of otalgia, tinnitus, and hearing loss in TMD patients were 36%, 27%, and 4% respectively. While in the control group the prevalences were otalgia 6%, tinnitus 10%, and hearing loss 1%. There were highly significant differences between the two groups regarding otalgia and tinnitus (p<0.01). The evaluation of the relationship between aural symptoms and TMD signs, yielded a significant positive correlation between otalgia with clicking, number of tender muscles, and TMJ tenderness. While it reversibly correlated with mouth opening. Tinnitus was found to be positively correlated with clicking and number of tender muscles. From the results of this research, dentist and otolaryngologist must act as a team in recognizing and diagnosing TMD and the otolaryngologists should refer patients with otalgic complaint without apparent ear diseases to a specialist in TMD for further evaluation